Antiplatelet therapy is associated with a high rate of intracranial hemorrhage in patients with head injuries - Patrick G Hughes; Scott M Alter; Benjamin A Mazer; Joshua J Solano; Richard D Shih; Mary J Hughes; Lisa M Clayton; Spencer W Greaves; Nhat Q Trinh (Trauma Surgery & Acute Care Open)
Background Antiplatelet agents are increasingly used in cardiovascular treatment. Limited research has been performed into risks of acute and delayed traumatic intracranial hemorrhage (ICH) in these patients who sustain head injuries. Our goal was to assess the overall odds and identify factors associated with ICH in patients on antiplatelet therapy.Methods A retrospective observational study was conducted at two level I trauma centers. Adult patients with head injuries on antiplatelet agents were enrolled from the hospitals’ trauma registries. Acute ICH was diagnosed by head CT. Observation and repeat CT to evaluate for delayed ICH was performed at clinicians’ discretion. Patients were stratified by antiplatelet type and analyzed by ICH outcome.Results Of 327 patients on antiplatelets who presented with blunt head trauma, 133 (40.7%) had acute ICH. Three (0.9%) had delayed ICH on repeat CT, were asymptomatic and did not require neurosurgical intervention. One with delayed ICH was on clopidogrel and two were on both clopidogrel and aspirin. Patients with delayed ICH compared with no ICH were older (94 vs 74 years) with higher injury severity scores (15.7 vs 4.4) and trended towards lower platelet counts (141 vs 216). Patients on aspirin had a higher acute ICH rate compared with patients on P2Y12 inhibitors (48% vs 30%, 18% difference, 95% CI 4 to 33; OR 2.18, 95% CI 1.15 to 4.13). No other group comparison had significant differences in ICH rate.Conclusions Patients on antiplatelet agents with head trauma have a high rate of ICH. Routine head CT is recommended. Patients infrequently developed delayed ICH. Routine repeat CT imaging does not appear to be necessary for all patients.Level of evidence Level III, prognostic.